Estudo fitoquímico, avaliação do potencial tóxico, citotóxico e inseticida dos extratos das folhas de Piptocarpha rotundifolia (Less.) Baker (Asteraceae) - Vieira, Tamires dos Santos (2017)
The objective of this work was to carry out phytochemical prospecting, to evaluate the toxicity, cytotoxic potential and potential insecticidal of Piptocarpha rotundifolia (Asteraceae). The plants are used with curative or prophylactic since antiquity, but it was the advancement of science that made possible the extraction of chemical constituents of plant species in order to correlate each active ingredient extracted with its pharmacological function, by means of the structure activity, thus giving rise to herbal drugs and synthetic or semi-synthetic originating from plantcampus of the Universidade Estadual de Goiás in Anapolis-GO. The samples were dried, pulverized in slicer and macerated with ethanol 96%. Ts.There are numerous plant species that do not have their phytochemical profile outlined, in this sense, this work aims the phytochemical study of Piptocarpha leaves rotundifolia (Asteraceae), a plant with occurrence in the Cerrado known popularly as Candeia. The collection of leaves was held on the he solvent was evaporated in rotary evaporated to obtain the crude ethanol extract. Soon after, this crude extract suffered a fractionation eluotrópica following order of solvents, giving rise to the extracts: hexane (PRFEH), dichloromethane (PRFED), ethyl acetate (PRFEA) and methanol (PRFEM). The fractionated obtained were subjected to chromatographic techniques for the purpose of isolation of substances. Extracts and isolated substances were tested in vitro by the MTT method (3- (4,5-Dimethylthiazol-2-yl) 2,5-Diphenyl Tetrazolium bromide) to evaluate the potential of cytotoxicity against tumor cell lines. That this test was satisfactory for some of the samples tested, the PRFEH - 40% extract showed inhibition of cell growth in the order of 93.15% for HCT - 116 cells, PRFEH - 50% presented inhibition of cell growth in the order of 84, 04% for SF-295 cells, 78.95% for PC-3 and 88.81% for HCT-116. The fractionated PRFEH-100% extract presented inhibition of cell growth in the order of 76.27% for SF-295 cells, 88.30% for PC-3 and 97.60% for HCT-116. The toxicity test against Artemia salina was performed according to the methodology proposed by Molina-Salinas and Said-Fernández (2006), and it was verified that only ethyl acetate fractionated extract showed weak toxicity against Artemia salina. The insecticide evaluation against the Atta sexdens rubropilosa ant was performed according to Bueno (1997) methodology and the extracts showed high toxicity values, the mortality rates obtained were above 70% for the concentration of 1 mg / mL and above 78% to 2 mg / mL, the extract with the best result being PRFEA with values of 100% and 98%, respectively.